2013
DOI: 10.1007/s11357-013-9578-z
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment for smoking does not alter the FOXO3A association with longevity

Abstract: Human longevity is a multifactorial phenotype influenced by both genetic and environmental factors. Despite its heritability of 25-32 %, the genetic background of longevity is as yet largely unexplained. Apart from APOE status, variation in the FOXO3A gene is the only confirmed genetic contributor to survival into old age. On the other hand, FOXO3A activity is known to be downregulated in various cancers, and the gene was recently identified as a novel deletion hotspot in human lung adenocarcinoma. In view of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…One major branch of this pathway extends through the Forkhead box class O 3A (FoxO3A) transcription factor. In multiple studies of unrelated human populations, Foxo3a variants have been associated with increased survivorship more extensively than polymorphisms for any other gene or locus (Willcox et al ., 2008; Anselmi et al ., 2009; Flachsbart et al ., 2009; Li et al ., 2009; Pawlikowska et al ., 2009; Soerensen et al ., 2010; Ziv & Hu, 2011; Däumer et al ., 2014). (The predominance of these single nucleotide polymorphisms in noncoding regions is reviewed in Donlon et al ., 2012; Flachsbart et al ., 2013.)…”
Section: Resultsmentioning
confidence: 99%
“…One major branch of this pathway extends through the Forkhead box class O 3A (FoxO3A) transcription factor. In multiple studies of unrelated human populations, Foxo3a variants have been associated with increased survivorship more extensively than polymorphisms for any other gene or locus (Willcox et al ., 2008; Anselmi et al ., 2009; Flachsbart et al ., 2009; Li et al ., 2009; Pawlikowska et al ., 2009; Soerensen et al ., 2010; Ziv & Hu, 2011; Däumer et al ., 2014). (The predominance of these single nucleotide polymorphisms in noncoding regions is reviewed in Donlon et al ., 2012; Flachsbart et al ., 2013.)…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 FOXO3 SNPs (rs2764264, rs2802292, rs12206094, rs7762395, rs9400239, rs479744, rs1935949, rs4946935, rs13217795, rs2802288, rs2153960, and rs13220810) reported to be associated with longevity, 9 SNPs (rs2764264, rs2802292, rs7762395, rs9400239, rs479744, rs13217795, rs2802288, rs2153960, and rs13220810) were included in this study and 3 SNPs (rs12206094, rs1935949, and rs4946935) were not included as only 1 study was available. The top 3 longevity-associated FOXO3 variants polymorphism (rs13217795, rs2764264, and rs2802292) and rs13220810 as a control were selected [18,2226,29,3236].…”
Section: Methodsmentioning
confidence: 99%
“…In 2014, a meta-analysis performed in four independent studies showed absence of association between SNP 10 and longevity [28]. However, later, SNP 10 was found to be significantly associated with longevity [29, 30] and bone fracture [31], one of aging phenotypes, in Caucasians.…”
Section: Discussionmentioning
confidence: 99%